Penerapan Metode Naive Bayes dalam Pengambilan Keputusan Pemilihan Bibit Cokelat Terbaik Pada Petani Kutacane - Fitria Permata Dara; Heri Haerudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Cocoa is a plant known as a chocolate producer. The contents of the cocoa beans can indeed be used and processed to become chocolate. Skill is one of the techniques or management skills in farming, by implementing various components of cultivation technology that provide a synergistic effect. In addition to skills, the experience of farmers is also very helpful and supports the ability to adopt technology in their farming business in order to produce good quality cocoa fruit. The purpose of this study is to make it easier for farmers to determine good cocoa seeds through a web-based system that can accommodate information in determining the best seeds from the experience of cocoa farmers in order to be able to classify the best chocolate seeds and store their data into databases using the Naive Bayes method using the PHP Programming Language and MySQL database as a storage medium.